Polyphosphate kinase regulates error-prone replication by DNA polymerase IV in Escherichia coli - Stumpf, Jeffrey D. (2005)
The ppk gene encodes polyphosphate kinase (Ppk), an enzyme that catalyses the polymerization of inorganic phosphate into long chains of polyphosphate (polyP). An insertion mutation in ppk causes a decrease in adaptive mutation in Escherichia coli strain FC40. Adaptive mutation in FC40 mostly results from error-prone DNA polymerase IV (Pol IV), encoded by dinB; most of the antimutagenic phenotype of the ppk mutant disappears in a dinB mutant strain. In addition, the ppk mutant causes a decrease in growth-dependent mutations produced by overexpressing Pol IV. However, the amount of Pol IV protein is unchanged in the ppk mutant strain, indicating that the activity or fidelity of Pol IV is altered. Adaptive mutation is inhibited both by the absence of Ppk, which results in low amounts of polyP, and by overproduction of Ppk, which results in high amounts of polyP, suggesting that an optimal level of polyP is necessary. Taken together, these results suggest a novel mechanism involving polyP that directly or indirectly regulates DNA polymerase activity or fidelity.